Healing pattern of bone defects covered by different membrane types - A histologic study in the porcine mandible - Frank P. Strietzel (2018)
Few investigations on guided bone regeneration (GBR) focus on the behaviour of tissues adjacent to barrier membranes. This study was conducted to (1) evaluate the barrier function potential of different resorbable and nonresorbable membranes for GBR, (2) investigate their structural changes after different intervals, and (3) characterize tissue composition and reaction adjacent to the barrier by qualitative histologic evaluation. Seven barriers for GBR were used per animal (made of dense or expanded polytetrafluoroethylene (d/ePTFE), titanium, polyetherurethane, collagen and two polylactide- polyglycolide-/-trimethylenecarbonate-co-polymers (PLPG, LPGTC) in standardized defects not exceeding the critical size) without using bone substitution material or autogenous bone at the right inferior margin of the mandibles of six domestic pigs. Samples of the defect areas with membranes were harvested after 2 days (one animal), 4 and 8 (two animals, each) and 12 weeks (one animal), respectively. The healing of bone defects was completed in all animals after 12 weeks. Nonresorbable barriers prevented the soft tissue in-growth into standardized defects. Thinner layers of fibrous tissue were seen underneath the dense and rigid barriers (dPTFE, titanium) when compared with collagen and PLPG/LPGTC, in which soft-tissue plugs occupied the crestal defect portion. PLPG-/LPGTC-barriers underwent structural changes after 4 weeks and revealed blistered central layers, whereas structural changes were not evident in nonresorbable barriers. The degradation of PLPG-/LPGTC-membranes was present with ingrowth of fibres, vessels, and cells. Using collagen or synthetic polymer barriers for GBR, the application of bone or bone substitutes to prevent membrane prolapse into the defect is suggested. © 2005 Wiley Periodicals, Inc.